Socio-cultural and Language Changes in a „Cultural Island”: Vershina – A Polish Village in Siberia - Głuszkowski, Michał (Eastern European Countryside, 2024)
The present article attempts to describe the social evolution of the community of Vershina, a village founded in the beginning of the 20th century by voluntary settlers from Little Poland, from a cultural island to the stage of assimilation. The social, economic, cultural, political and language situation of the community changed several times. The most significant historical moments of Russia and the Soviet Union set the borders of three main periods in Vershina’s history. During its first two-three decades Vershina consisted a homogenous Polish cultural and language island. The migrants preserved the Roman Catholic religion, Polish language and traditions as well as farming methods and machines. Collectivization and the communist system with its repressions made the Polish village assimilate to its surroundings. With the flow of time, the generation of first settlers died and some of the traditions of Little Poland vanished or got modified by the elements of the Soviet, Russian or Buryat culture. After the Perestroika the minorities gained some rights, which strengthened in the 1990s. Thanks, to the political changes and the collapse of the SU the inhabitants of Vershina can found cultural organisations, cultivate their religion, and learn Polish in local schools. However, in spite of the regained rights, over the decades of mass sovietization and ateization, the culture and customs of the Polish community became similar to other Siberian villages. Young people from the group of our interest abandon their mother language and are not eager to leave Russia and move to Poland. The process of assimilation is intensifying while there are practically no factors protecting the local culture and language.